The neurotoxicity of trichothecenes T-2 toxin and deoxynivalenol (DON): Current status and future perspectives - Zhang, Jiajia; You, Li; Wu, Wenda; Wang, Xu; Chrienova, Zofia; Nepovimova, Eugenie; Wu, Qinghua; Kuca, Kamil (Food and chemical toxicology, 2020)
During the last decade, the neurotoxicity of the trichothecenes T-2 toxin and deoxynivalenol (DON) has been a major concern, and many important findings have been reported on this topic. Through a summary of relevant research reports in recent years, we discuss the potential neurotoxic mechanisms of T-2 toxin and DON. In neuronal cells, T-2 toxin induces mitochondrial dysfunction and oxidative stress through a series of signalling pathways, including Nrf2/HO-1 and p53. This toxin crosses the blood-brain barrier (BBB) by altering permeability and induces oxidative stress responses, including ROS generation, lipid peroxidation, and protein carbonyl formation. Cellular metabolites (for example, HT-2 toxin) further promote neurotoxic effects. The type B trichothecene DON induces neuronal cell apoptosis via the MAPK and mitochondrial apoptosis pathways. This molecule induces inflammation of the central nervous system, increasing the expression of proinflammatory molecules. DON directly affects brain neurons and glial cells after passing through the BBB and affects the vitality and function of astrocytes and microglia. Exposure to trichothecenes alters brain dopamine levels, decreases ganglion area, and further induces brain damage. In this review, we mainly discuss the neurotoxicity of T-2 toxin and DON. However, our main goal was to reveal the potential mechanism(s) and offer new topics, including the potential of hypoxia-inducible factors, immune evasion, and exosomes, for future research in this context. This review should help elucidate the neurotoxic mechanism of trichothecenes and provides some potential inspiration for the follow-up study of neurotoxicity of mycotoxins.
Keywords: Brain damage; Animals; apoptóza; neurotoxiny; oxidační stres; Deoxynivalenol; Apoptosis; T-2 Toxin; Oxidative Stress; T-2 toxin; Blood-brain barrier; lidé; neurony; signální transdukce; Signal Transduction; Neurons; Trichothecenes; Neurotoxins; Oxidative stress; Neurotoxicity; trichotheceny; zvířata; Humans